Inheritance of soybean resistance to soybean rust in Uganda’s soybean germplasm - Gebremedhn, Hailay Mehari; Belay Weldekidan, Miesho; Msiska, Ulemu Mercy; Asmamaw, Fentaw Abate; Lapaka Odong, Thomas; Tukamuhabwa, Phinehas; Rubaihayo, Patrick (International Journal of Agronomy and Agricultural Research, 2018)
Understanding the genetic mechanisms of soybean rust resistance is important for effective selection and breeding procedures. This study was hence conducted to determine the combining ability and gene action controlling soybean rust using a 10x10 half diallel mating design. The F2 segregating populations along with their parents were evaluated for rust severity and sporulation level at two reproductive stages (R4 and R6) in screen house and field conditions during the second season of 2016 and first season of 2017 at MUARIK using an alpha lattice design replicated thrice. Significant differences were observed among the parents and F2 generations for both disease severity and sporulation level. General and specific combining abilities were highly significant. The GCA/SCA ratio (1.50-2.30) and the Baker’s ratio (0.75-0.82) showed the predominance of additive gene action in the inheritance of soybean rust resistance. The broad-sense (0.94-0.99) and narrow-sense (0.73-0.82) heritability estimates indicated the possibility of improving resistance to soybean rust through selection in the early generations. UG 5, Maksoy 3N, Maksoy 4N and Maksoy 5N had negative GCA effects. The F2 populations derived from these parents crossed with Wonder soya and Nam 2 had also negative SCA effects. The use of these parents and F2 populations can, therefore, increase the response to selection for improving resistance to soybean rust.
Keywords: Phakopsora pachyrhizi; Rust severity; GCA; SCA; Additive gene action introduction